Qualitative Analysis of Community Perceptions in Situ Gunung on the Impact of Tourism Activities in the Gunung Gede Pangrango National Park Area - Kristanto, Eko; Meitolo Hulu (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
The Covid-19 pandemic has ushered in shifts in tourist behavior, impacting their preferences for tourist attractions and activities (Kemenparekraf, 2023). Tourists now gravitate towards serene and picturesque settings in villages, at the foothills of mountains, or within pristine environments like forests in national parks. This trend has notably bolstered the advancement of ecotourism in Indonesia. Statistics indicate a significant preference for glamorous camping or glamping among tourists (45.9%), surpassing the choice of resort accommodations (24.7%) (Kemenparekraf, 2023). However, these transformations come with adverse effects, notably the disruption of the tranquil ambiance cherished by local residents due to the influx of tourists, leading to clashes between diverse cultures and traditional customs (Joseph & Maiwa, 2011). Concurrently, local perceptions of tourism significantly shape its development. Thus, this study aims to scrutinize people's perceptions of natural tourist destinations, specifically focusing on Situ Gunung. By analyzing data from 10 interview sources using techniques like word frequency and contextual analysis, this research identifies factors influencing local community perceptions of tourism, including age, length of stay, involvement in tourism activities, and personal experiences.